Children With Enthesitis‐Related Arthritis and Possible Benefits From Treatments for Adults With Spondyloarthritis. Issue 7 (15th April 2022) - Weiss, Pamela F.; Fuhlbrigge, Robert C.; von Scheven, Emily; Lovell, Daniel J.; Colbert, Robert A.; Brunner, Hermine I.; ,
Abstract : This review will summarize clinical, genetic, and pathophysiologic characteristics that are shared between children with enthesitis‐related arthritis (ERA) with axial involvement and adults with nonradiographic (and in some cases radiographic) axial spondyloarthritis (SpA), as well as between children with ERA and primarily peripheral disease manifestations and adults with peripheral SpA. Due to the differences in classification criteria for children with ERA and adults with axial and peripheral SpA, the US Food and Drug Administration (FDA) granted automatic full waivers of studies in children for new medications for "axial spondyloarthropathies including ankylosing spondylitis" up until July 2020. Thus, although current juvenile idiopathic arthritis treatment guidelines recommend the use of biologic disease‐modifying antirheumatic drugs as part of the early treatment for patients with ERA, none of the FDA‐approved therapies for peripheral SpA or nonradiographic axial SpA (certolizumab pegol, ixekizumab, and secukinumab) have been studied or are labeled for use in children with ERA. Considering the similarities between adult SpA and ERA in terms of etiology, genetics, pathogenesis, and clinical manifestations summarized in this review, medications approved for axial SpA or peripheral SpA should also be studied in children with active ERA involving axial or peripheral joints, respectively, with the intent to achieve labeling for use in children. Considering the current lack of effective FDA‐approved therapies for ERA, the FDA should also consider requiring pediatric studies for medications that have already been approved for the treatment of adults with SpA.